Three new species of Periploma (Bivalvia, Periplomatidae) from the Panamic Province - Valentich-Scott, Paul; Coan, Eugene V. (Zootaxa, 2010)
While preparing a manual on the marine bivalves of the Panamic Province, we have found three species of the Periplomatidae that lack names. In this paper, we describe two new species from Mexico, Periploma skoglundae and P. hendrickxi, and one new species from El Salvador, P. kaiserae.